ANALISIS FENETIK JAGUNG RAS LOKAL NUSA TENGGARA TIMUR UMUR GENJAH BERDASARKAN KARAKTER AGRONOMI DAN INTER SHORT SEQUENCE REPEATS - Kusumadewi Sri Yulita; Charles Y. Bora; IGB Adwita Arsa; Tri Murniningsih (BERITA BIOLOGI, 2015)
Maize having maturity age less than 80 HST (days after planting) has played an important roles as part of food security system for the people of NTT since they can be harvested earlier than common maize and usually consumed by children. Local landraces of maize are usually heterogenous homozygote due to traditional farming system where the farmers used their own harvested maize for generations resulted in low level of heterogeinity. This study was aimed to assess phenotypic and genetic variability among 12 accessions of local maize on the basis of their agronomic perfomance and Inter Short Sequence Repeats profiles. Two accessions of non- early maturity maize were included as control. Ten agronomic traits and eight ISSRs ‘s primers were used to perform a phenetic analysis using unweighted pair group method with aritmethical average(UPGMA).Clustering dendrogram based on agronomic characters suggested that all accessions were forming three groups on the basis of their maturity (very early mature, early mature, and intermediate mature).On the other hand, analysis using ISSR profiles resulted on random grouping across the accesions.All accessions of early mature age having taxonomic distance of 0.83 and genetic similarity of 57%. This indicated that even though the landraces were open pollinated which allowed cross pollinations during the flowering time, phenotipic and genotipic variations observed to be considerably low.